The impact of weight loss on thyroid autoimmunity - Weight loss decreases thyroid peroxidase antibody levels: a retrospective cohort study - Mutlu, Hacer Hicran; Mutlu, Hasan Hüseyin (The European Research Journal, 2021)
Objectives: Within the last two decades, an increase has been seen both in autoimmune diseases and obesity, therefore, the correlation between obesity and autoimmunity has been questioned and many studies have been conducted on this issue. Based on this relationship, we aimed to determine whether the weight loss affects the thyroid peroxidase (TPO) antibody levels of obese individuals with thyroid autoimmunity or not. Methods: The patients who were aged over 18 years, had a Body Mass Index (BMI) ≥ 30 Kg/m2 and TPO antibody ≥ 5.60 IU/mL were included in the study. The primary endpoint was the change in TPO antibody levels of the patients at the end of the sixth month of the follow-up. The correlations of TPO antibody levels with anthropometric and laboratory measurements were evaluated. Results: At the end of the sixth month of follow-up of the patients, TPO antibody levels decreased after weight loss (p < 0.001). No significant correlations were found between the differences in weight, fat mass, muscle mass and TPO antibody levels (p = 0.171; p = 0.656; p = 0.939). Conclusions: Weight loss caused a decrease in the levels of TPO antibody levels in the obese individuals having thyroid autoimmunity pointing that weight loss might be useful to stop the progression or lead to regression of the disease.